DAMPAK LINGKUNGAN DAN SOSIAL TERHADAP MINAT WISATAWAN DI KEBUN RAYA BOGOR - Liliana Dewi; Ahmad Naisaburi Bintang Dhia; Ariyah Afifah; Firas Rahmanikram Susetya; Livia Miftahulhasanah; Nawina Sharen; Siti Choerunisa (Jurnal Inovasi Penelitian, 2021)
The environment is a condition that affects the development and behavior of living things. Social itself is a way in which each individual has related to others. The interest of tourist are the source of motivation that encourages someone to do what they want. So it’s profitable then they will feel interested and bring their own satisfaction and if the satisfaction is reduced then the interest will decrease. For this reason, with the interest of tourist, there is a development of an object of attraction from tourism that is included in the category of tourist attraction. The results of research in the field show that the Bogor Botanical Gardens, which have been established since 1819, are the center for plant research and conservation. Over time, the Bogor Botanical Gardens issued 5 pillars namely Conservation, Education, Research, Nature Tourism and Environmental Services. From these pillars, it states that the Bogor